Effect of Moringa oleifera on haematological parameters: a systematic review - Chiara Perera; D. I. Galappatti; A. M. Thrimavithana; Iresha Jayawickrama; Buddhika Mahesh; Mahendra Arnold; Ruwan Ferdinando; Wasantha Gunathunga (College of Community Physicians of Sri Lanka, 2022)
Background: Moringa (Moringa oleifera) is a plant found in many regions. Its extracts, especially of leaves, are a rich source of fibre, proteins and micronutrients including iron, thus potentially be used for haematological-applications including iron-deficiency-anaemia, affecting approximately one-third of the global population. Aims: To systematically-review the effect of moringa on haematological-parameters. Methods: Preferred-Reporting-Items-for-Systematic-Reviews (PRISMA) guidelines were followed. PubMed, Cochrane-library, Agricola, CINAHL and EMBASE databases were searched. Selection of articles were done in three rounds by two independent reviewers intervened by a third, resolving conflicts. Human-studies on Moringa with relevant outcomes were included. Risk-of-bias assessment was done with Grading-of-Recommendations-Assessment-Development-and-Evaluation (GRADE) criteria. Heterogeneity was assessed and results were narratively-synthesized without meta-analysis. Registration from International-Prospective-Register-of-Systematic-Reviews (ID: CRD42020181432) was obtained. Results: Following de-duplication there were 213 articles. Six studies on Moringa-leaf extracts, covering nine outcomes were included. Four studies included children below 2 years and two included reproductive and post-menopausal women. Among children under 2 years, mean improvement in heamoglobin-level ranged between 0.31-2.6g/dl with a reduction of the prevalence of anaemia by 53% (95%CI:35.1-72.0;p<0.001). Haemoglobin-level among anaemic women in reproductive-ages showed an improvement with a mean difference (MD) of 0.794(SD 0.81)(p <0.05) in the interventional group, and in the control group, the MD was 0.644(SD 0.83). Post-menopausal-women showed a significant improvement of 17.5% in haemoglobin compared to baseline values (p ≥0.01). Two studies showed improvements in ferritin-levels with a MD of 29.378ng/mL (SD 42.48) (p-0.012) among anaemic women and 31.9 (SD 23.8) MD among children under 2 years. One study showed an improvement [MD(SD)] in erythrocyte count 0.482(2.26), hematocrit 0.947(4.56), MCV 0.635(11.22), MCH 1.312(4.94), MCHC 2.459(2.86), and RDW 1.400(2.07) compared to the control group. Conclusions and Recommendations: Moringa-leaf extracts as a natural supplement, is seemingly useful for improving haematological parameters, especially in improving the haemoglobin level among children and female adults.